Possible Consequences of the Economic Cooperation between the EU and East-Asian States - Żurowska, Katarzyna (Możliwe skutki współpracy gospodarczej między UE a państwami Azji Południowej i Wschodniej, 2010)
Taking into consideration two basic conditions which decide about the future shape of relations between the EU and East and South Asian economics, i.e.: (1) the share of mutual turnover in the total turnover of each of the markets, and (2) preparedness as well as readiness for deepening of integration in the region, leading towards introduction of a regional common currency in ASEAN, one can try to forecast the impact of such a move on mutual economic contacts between the EU and ASEAN or wider EU-ASEAN+3 or ASEAN+5. This task can be considered as the main goal of this paper. The study introduces two scenarios for the future cooperation in monetary sphere for the region: a common Asian currency and as an alternative - a common world currency.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 90-102
Keywords: economic cooperation; ASEAN; integration